Low-Code Integration Platforms: Revolutionizing Enterprise Architecture Through AI-Driven Development - Krishna Kanth Kothapally (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The widespread adoption of low-code platforms is fundamentally transforming enterprise integration strategies, offering a paradigm shift in how organizations approach system connectivity and application development. This article examines the architectural framework, implementation patterns, and transformative impact of low-code platforms in enterprise environments, with particular emphasis on their role in democratizing integration development. This article explores how these platforms bridge the traditional divide between IT and business teams while enabling rapid prototyping and iteration of integration solutions. The discussion encompasses the emerging role of artificial intelligence and machine learning in enhancing low-code capabilities, alongside critical considerations for security, governance, and scalability. Through analysis of industry practices and architectural patterns, this article presents a comprehensive framework for organizations to evaluate, implement, and optimize low-code integration platforms while maintaining enterprise-grade reliability and performance. This article suggests that low-code platforms represent a strategic imperative for organizations seeking to accelerate their digital transformation initiatives while maintaining robust integration architectures.